GOLPH3 promotes endotoxemia-induced liver and kidney injury through Golgi stress-mediated apoptosis and inflammatory response - Theodomir Dusabimana; Jihyun Je; Seung Pil Yun; Hye Jung Kim; Hwajin Kim; Sang Won Park (Cell Death and Disease, 2023)
Abstract Sepsis is a serious clinical condition characterized by a systemic inflammatory response, a leading cause of acute liver and kidney injury, and is associated with a high morbidity and mortality. Understanding the molecular mechanisms underlying the acute liver and kidney injury is crucial for developing an effective therapy. Golgi apparatus plays important roles and has various substrates mediating cellular stress responses. Golgi phosphoprotein 3 (GOLPH3), linking Golgi membranes to the cytoskeleton, has been identified as an important oncogenic regulator; however, its role in endotoxemia-induced acute liver and kidney injury remains elusive. Here, we found that upregulation of GOLPH3 was associated with endotoxemia-induced acute liver and kidney injury. Lipopolysaccharide (LPS) treatment increased Golgi stress and fragmentation, and associated pro-inflammatory mediator (Tnfα, IL-6, and IL-1β) production in vivo and in vitro. Interestingly, the downregulation of GOLPH3 significantly decreased LPS-induced Golgi stress and pro-inflammatory mediators (Tnfα, IL-6, Mcp1, and Nos2), and reversed apoptotic cell deaths in LPS-treated hepatocytes and renal tubular cells. GOLPH3 knockdown also reduced inflammatory response in LPS-treated macrophages. The AKT/NF-kB signaling pathway was suppressed in GOLPH3 knockdown, which may be associated with a reduction of inflammatory response and apoptosis and the recovery of Golgi morphology and function. Taken together, GOLPH3 plays a crucial role in the development and progression of acute liver and kidney injury by promoting Golgi stress and increasing inflammatory response and apoptosis, suggesting GOLPH3 as a potential therapeutic target for endotoxemia-induced tissue injury.